(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study aimed to determine the utilization of e-wallets as perceived by ABM students at Bestlink College of the Philippines during the 2022-2023 academic year. The result of this study revealed that the majority of respondents were young females who preferred Gcash. The respondents had a positive utilization of e-wallets, with some concerns about security and privacy policies. The study recommended that e-wallet providers offer training sessions and educational materials, improve user experience and security measures, establish partnerships with local merchants, and gather feedback. The proposed outputs included developing training modules, improving user experience, implementing additional security measures, partnering with local merchants, and establishing feedback mechanisms.